1999
DOI: 10.1073/pnas.96.9.5043
|View full text |Cite
|
Sign up to set email alerts
|

Situs inversus and embryonic ciliary morphogenesis defects in mouse mutants lacking the KIF3A subunit of kinesin-II

Abstract: The embryonic cellular events that set the asymmetry of the genetic control circuit controlling left-right (L-R) axis determination in mammals are poorly understood. New insight into this problem was obtained by analyzing mouse mutants lacking the KIF3A motor subunit of the kinesin-II motor complex. Embryos lacking KIF3A die at 10 days postcoitum, exhibit randomized establishment of L-R asymmetry, and display numerous structural abnormalities. The earliest detectable abnormality in KIF3A mutant embryos is foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
409
0
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 497 publications
(425 citation statements)
references
References 41 publications
13
409
0
3
Order By: Relevance
“…Other mutant strains used were Gli3 XT-J , an intragenic deletion allele (6); Ptch1 tm1Mps , a lacZ gene insertion allele (7); nodal tm1Rob , a lacZ gene insertion allele (8); and Kif3a tm1Maz , a targeted null allele (9). Mutant alleles were genotyped as described (3,(5)(6)(7)(8)(9).…”
Section: Methodsmentioning
confidence: 99%
“…Other mutant strains used were Gli3 XT-J , an intragenic deletion allele (6); Ptch1 tm1Mps , a lacZ gene insertion allele (7); nodal tm1Rob , a lacZ gene insertion allele (8); and Kif3a tm1Maz , a targeted null allele (9). Mutant alleles were genotyped as described (3,(5)(6)(7)(8)(9).…”
Section: Methodsmentioning
confidence: 99%
“…Many treatments affecting LR asymmetry result in 20–40% heterotaxia, a much lower level than the 50–90% expected (depending on the number of organs assessed), an issue that is rarely if ever discussed [see for example (Nagai et al, 2010; Fogelgren et al, 2011; Marszalek et al, 1999; Bajoghli et al, 2007; Amack et al, 2007; Danilchik et al, 2006)]. A considerable number of studies on the mechanisms of LR asymmetry are available and comparable endpoints (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, motility of naturally occurring central pairless cilia and flagella has been reported [Baccetti et al, 1979;Prensier et al, 1980;Nonaka et al, 1998]. Most notably, recent studies have demonstrated that the 9ϩ0 nodal cilia of developing embryos are motile, and this motility plays a critical role in establishing left-right asymmetry [Nonaka et al, 1998;Marszalek et al, 1999;Nonaka et al, 2002].…”
Section: Introductionmentioning
confidence: 99%